Study of Particle Velocity Impact on The Surface of M-152 Steel and SiCp/Ti- 6Al-4V Metal Matrix Composite - Mohamad Yasin, Muhammad Hilman (IRC, 2021)
Rapid development of titanium matrix composite (TMC) due to the development of particulate reinforced of silicon carbide particulate (SiCp) in metal matrix composite.